PPGD/EBA/UFRJ: Developments in Theory-Practice Research in Graduate Design studies - Pires, Julie; Kosminsky, Doris; Irigoyen, Gabriela (DAT Journal, 2026)
This article adopts a qualitative and exploratory approach to reflect on the creation and implementation of the PhD program in the Graduate Program in Design at the School of Fine Arts of the Federal University of Rio de Janeiro (PPGD/EBA/UFRJ), relating this institutional experience to current debates on design research and theory–practice methodologies in the field of Visual Design. The program began in 2017 with the Master’s degree, and the PhD was approved in 2024 and launched in 2025. Its proposal emphasizes critical and experimental theory–practice research committed to sustainability, inclusion, and contemporary demands. The article makes explicit the program’s epistemological legacies and engages with contributions by Bomfim, Frayling, and Redström. Based on this theoretical framework and on the analysis of research developed within the program, it proposes a typology of three axes of theory–practice articulation: Poetics of making (process and materiality as evidence), Critical-analytical modellings (analytical instruments and critical-visual arguments), and Guideline-oriented iterativity (transferable syntheses). Finally, it argues that the interdependence of theory and practice is central to contemporary academic debates in design and, within the PPGD/EBA/UFRJ, is operationalized through the proposed typology.